Régimen de humedad de un suelo de la altillanura cultivado con arroz de secano bajo diferentes intensidades de laboreo - Valenzuela, I.G.; Perea, G; Amézquita Collazos, Edgar; García, A. (2001)
To evaluate the influence of tillage intensity on soil physical properties, related to water movement and to relate these characteristics to water storage capacity and water depletion in an Oxisol of the Oriental Plains of Colombia a Typic Haplustox Isohyperthermic caolinitic soil of Puerto López (Meta) was selected. Several treat ments of tillage intensity were evaluated: 6, 12 and 24 harrowing pases which were compared to native sa vanna. In each treatment the soil was sampled at O 5, 5 10, l0 20, 20 30, 30 5O and 5O 7O cm in different times of the rainy and summer seasons. The soil physical properties related to soil water movement were determined. Highly significant differences be tween the Savanna and the tillage treatments were found which indicated that tillage intensity causes a decrease in the soil water retention capacity, but infil tration increases due to the breaking of the surface crust ing. Tilage caused decrease in the soil water content in the upper 20 cm, but an increase from this depth to the bottom of the soil profile. Not agronomic limitations on soil airspace were found, due to an appropiate amount of macropores that facilitate the water infiltration and soil water movement but the soil structure has not re sistance to the rain drop impact and the soil becomes sealed and crusted. Using tillage it is possible to destroy this crust to get better aeration and water infiltration but this effect is temporary.